Polymer, electrolyte material, electrolyte membrane, electrolyte membrane with catalyst layer, membrane electrode assembly, solid polymer-type fuel cell, and solid polymer-type water electrolysis device
Patent Information
- Application Number
- JP2024191158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-01-29
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2044-03-26
AI Technical Summary
【0025】 本開示の一側面によれば、電解質としてのプロトン伝導性に優れるポリマーを提供することができる。
Smart Images

Figure 2025023971000046 
Figure 2025023971000001 
Figure 2025023971000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a polymer, an electrolyte material, an electrolyte membrane, an electrolyte membrane with a catalyst layer, a membrane electrode assembly, a polymer electrolyte fuel cell, and a polymer electrolyte water electrolysis device. [Background technology]
[0002] In recent years, fuel cells have been in the spotlight as a new, highly energy-efficient energy technology against the backdrop of environmental issues. Among them, solid polymer fuel cells, which use polymer materials as electrolytes, have attracted particular attention because they have a high maximum current density and operate at low temperatures, making them suitable for use as a mobile power source for automobiles and other vehicles, as well as small-capacity power sources for portable electronic devices. Furthermore, from the perspective of carbon neutrality, the use of solid polymer hydrogen energy that applies fuel cell technology has also attracted attention.
[0003] Fluorine-based polymers are known as polymers (electrolyte polymers) used as electrolytes in polymer electrolyte fuel cells and water electrolysis (see, for example, Patent Document 1). Fluorine-based polymers are widely used in electrolyte applications due to their high proton conductivity, but have problems such as high cost and high environmental impact.
[0004] For these reasons, development of electrolyte polymers that do not use fluorine is also underway. For example, Patent Document 2 discloses an invention relating to a polymer electrolyte membrane made of a block copolymer containing one or more segments (A1) containing an ionic group and one or more segments (A2) not containing an ionic group. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-204119 [Patent Document 2] International Publication No. 2013-031675 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the non-fluorinated polymer obtained by block copolymerization as disclosed in the above Patent Document 2 does not necessarily have sufficient proton conductivity.
[0007] An object of one aspect of the present disclosure is to provide a polymer having excellent proton conductivity as an electrolyte. [Means for solving the problem]
[0008] In some aspects, the present disclosure provides the following [1] to
[16] .
[0009] [1] A polymer having a structure represented by the following formula (1): [ka] [In formula (1), A 1 represents a structural unit represented by the following formula (a1): A 2 represents a structural unit represented by the following formula (a2): L 1 and L 2 each independently represents a single bond, -O-, -S- or -SO2-; n represents an integer from 10 to 100; * indicates a bond. Multiple A's 1 are identical to each other, Multiple A's 2 are identical to each other, Multiple L's 1 may be the same or different, Multiple L's 2 may be the same or different. [ka] [In formula (a1), IExG represents an ion exchange group, L 3 represents a single bond, -O-, -S-, -SO2- or -CO-; x represents an integer from 2 to 10; * indicates a bond. The multiple IExGs may be identical to or different from each other, Multiple L's 3 may be the same or different. [ka] [In formula (a2), Ar represents an arylene group having no ion exchange group; L 4 represents a single bond, -O-, -S-, -SO2- or -CO-; y represents an integer from 3 to 20; * indicates a bond. A plurality of Ar may be the same or different, Multiple L's 4 may be the same or different.
[0010] [2] Said L 1 , said L 2 , said L 3 and the above L 4 are each independently a single bond or -SO2-.
[0011] [3] The polymer according to [1] or [2], wherein the constitutional unit represented by the formula (a1) contains, as the ion exchange group, at least one selected from the group consisting of a sulfone group, an alkylsulfone group, and a sulfonimide group.
[0012] [4] The polymer according to any one of [1] to [3], wherein the constitutional unit represented by the formula (a2) contains, as the arylene group, at least one selected from the group consisting of a phenylene group, a naphthylene group, and a fluorene group.
[0013] [5] The polymer according to any one of [1] to [4], having a number average molecular weight of 20,000 to 300,000.
[0014] [6] The polymer according to any one of [1] to [5], which is a polymer of a compound represented by the following formula (b1) and a compound represented by the following formula (b2), or an oxide thereof. [ka] [In formula (b1), A 1 is as defined above, and X 1b and X 2b each independently represents a halogen atom. [ka] [In formula (b2), A 2 is as defined above, and Z 1b and Z 2b each independently represents a hydroxy group, a thiol group, a halogen atom, a boronic acid group, an alkylborane group, or a boronic acid ester group.
[0015] [7] The polymer comprises a plurality of polymer units each having a structure represented by formula (1), The polymer according to any one of [1] to [6], having three or more crosslinking groups bonded to the polymer units.
[0016] [8] the bridging group has one or more aromatic rings, The polymer according to [7], wherein the polymer unit is bonded to the aromatic ring.
[0017] [9] The polymer according to [7] or [8], which is a reaction product of a polymer of a compound represented by the following formula (b1) and a compound represented by the following formula (b2) or an oxide thereof, and a compound having three or more groups that react with the polymer or the oxide thereof to form a crosslink: [ka] [In formula (b1), A 1 is as defined above, and X 1b and X 2b each independently represents a halogen atom. [ka] [In formula (b2), A 2 is as defined above, and Z 1b and Z 2b each independently represents a hydroxy group, a thiol group, a halogen atom, a boronic acid group, an alkylborane group, or a boronic acid ester group.
[0018]
[10] The polymer according to any one of [1] to [9], wherein the ratio of the weight average molecular weight to the number average molecular weight is 2.0 to 20.0.
[0019]
[11] An electrolyte material comprising the polymer according to any one of [1] to
[10] .
[0020]
[12] An electrolyte membrane comprising the polymer according to any one of [1] to
[10] .
[0021]
[13]
[12] A catalyst layer-attached electrolyte membrane comprising: the electrolyte membrane according to
[12] ; and a catalyst layer disposed on one or both sides of the electrolyte membrane.
[0022]
[14]
[12] A membrane electrode assembly comprising the electrolyte membrane according to
[12] and an electrode layer disposed on one or both sides of the electrolyte membrane.
[0023]
[15] A polymer electrolyte fuel cell comprising the membrane electrode assembly according to
[14] .
[0024]
[16] A solid polymer water electrolysis apparatus comprising the membrane electrode assembly according to
[14] . Effect of the Invention
[0025] According to one aspect of the present disclosure, a polymer having excellent proton conductivity as an electrolyte can be provided. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a graph showing the SAXS scattering intensity of the electrolyte membrane of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, exemplary embodiments of the present disclosure will be described. However, the present disclosure is not limited to the following embodiments. In this specification, a numerical range indicated using "~" indicates a range including the numerical values before and after "~" as the minimum and maximum values, respectively. In addition, unless specifically stated otherwise, the units of the numerical values before and after "~" are the same. In addition, the upper limit and lower limit values individually stated can be combined in any combination.
[0028] <Polymer> The polymer of one embodiment (hereinafter also referred to as "polymer (P)") has a structure represented by the following formula (1).
[0029] [ka]
[0030] In formula (1), A 1 is a structural unit represented by the following formula (a1) (hereinafter, “structural unit A 1") and A 2 is a structural unit represented by the following formula (a2) (hereinafter, “structural unit A 2 It is also called ". ) and L 1 and L 2 each independently represents a single bond, -O-, -S- or -SO2-, n represents an integer of 10 to 100, and * represents a bond. 1 are identical to each other, and multiple A 2 are identical to each other, and multiple L 1 may be the same or different, and multiple L 2 may be the same or different from each other.
[0031] [ka]
[0032] In formula (a1), IExG represents an ion exchange group, L 3 represents a single bond, -O-, -S-, -SO2- or -CO-, x represents an integer of 2 to 10, and * represents a bond. 3 may be the same or different from each other.
[0033] [ka]
[0034] In formula (a2), Ar represents an arylene group having no ion exchange group, L 4 represents a single bond, -O-, -S-, -SO2- or -CO-; y represents an integer of 3 to 20; * represents a bond. A plurality of Ar may be the same or different, and a plurality of L 4 may be the same or different from each other.
[0035] The polymer (P) is a so-called electrolyte polymer and has excellent proton conductivity. Therefore, a membrane (polymer electrolyte membrane) formed from the polymer (P) exhibits excellent proton conductivity. The reason why the polymer (P) has excellent proton conductivity is not clear, but it is believed that the polymer (P) has a structure in which the polymer (P) has a plurality of identical hydrophilic structural units A. 1 (hydrophilic portion) and multiple hydrophobic structural units A that are identical to each other 2 Since the structural unit A (hydrophobic portion) is precisely arranged, the ion exchange groups are arranged at equal intervals, and it is presumed that the ion exchange groups are self-assembled in a higher order structure to induce a microphase separation structure, which is presumed to form a good proton conductive path within the polymer (P). 1 The presence of three or more ion exchange groups densely packed in the porous membrane is also believed to contribute to the improvement of phase separation and proton conductivity. The above effect is particularly noticeable in a high humidity environment (e.g., humidity of 80% RH or higher).
[0036] The polymer (P) also tends to have excellent gas barrier properties when made into a film. The reason for this is presumed to be as follows: Since the polymer (P) has a main chain composed of an arylene group containing a benzene ring, the solubility of hydrogen and oxygen is low, and the segment motion is restricted, suppressing gas diffusion in the film, which is thought to result in excellent gas barrier properties when made into a film.
[0037] (Polymer (P)) As represented by formula (1), the polymer (P) comprises a structural unit A 1 and building block A 2 and the linking group (L 1 Or L 2 ) between adjacent repeating structures (the structure in [ ] in formula (1)). The repeating number (n) of the structure is 10 to 100, and may be 15 or more or 20 or more, and may be 80 or less or 50 or less. When the repeating number (n) is 15 or more, the gas barrier property tends to be excellent, and when the repeating number (n) is 50 or less, the solubility in a solvent and the film-forming property tend to be excellent. The repeating number (n) of the structure is preferably 15 to 80, and more preferably 20 to 50.
[0038] [Structural unit A 1 ] Building block A 1 The aromatic ring having an ion exchange group (IExG) is connected to a linking group (L 3 ) and has a continuous structure.
[0039] Ion exchange groups, also called ionic groups, have the property of releasing ions (e.g., cations) to exchange with other ions. Examples of ion exchange groups include sulfone groups, alkylsulfone groups, perfluoroalkylsulfone groups, sulfonimide groups, phosphonic acid groups, phosphoric acid groups, and carboxy groups. These ion exchange groups also include those that are in the form of salts. For example, a "sulfone group" is -SO3M 1 / q (M represents H or a metal (e.g., Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, Ti, Al, Fe, Pt, Rh, Ru, Ir, Pd), and q represents the valence of M (e.g., an integer from 1 to 4). The metal represented by M exists as an ion (cation) and is represented by -SO3 - and forms salt.
[0040] An alkylsulfone group is, for example, -R 1 SO3M 1 / q It is expressed as R 1 R is an alkanediyl group, the number of carbon atoms of which is preferably 1 to 12. 1 Specific examples of include a methylene group, a butane-1,4-diyl group, and a hexane-1,6-diyl group. M and q are as defined above.
[0041] The sulfonimide group is, for example, -SO2NM 1 / q SO2R 2 It is expressed as R 2 R is an alkyl group, the number of carbon atoms of which is preferably 1 to 6. 2 Specific examples of the group include a methyl group, an ethyl group, and a propyl group. M and q are as defined above.
[0042] Building block A 1From the viewpoint of obtaining better proton conductivity, the structural unit A preferably contains, as an ion exchange group, at least one group selected from the group consisting of a sulfone group, an alkylsulfone group, and a sulfonimide group, and more preferably contains a sulfone group. 1 It is more preferable that the majority of the ion exchange groups present in the structural unit A are those of the above-mentioned preferred embodiment. 1 It is particularly preferred that all of the ion exchange groups present therein are of the above-mentioned preferred embodiment.
[0043] Building block A 1 From the viewpoint of obtaining better proton conductivity, 3 From the same viewpoint, the structural unit A preferably contains at least one group selected from the group consisting of -SO2- and -CO-, and more preferably contains -SO2-. 1 There are multiple linking groups (L 3 It is further preferred that the majority of the above-mentioned preferred embodiments.
[0044] Building block A 1 The linking group (L 3 ) is preferably a single bond or -SO2- from the viewpoint of achieving both better proton conductivity and chemical durability.
[0045] Linking group (L 3 The bonding position of the structural unit A is not particularly limited, but is preferably the ortho or meta position relative to the ion exchange group, and more preferably the ortho position. 1 It is preferable that the copolymer contains a 1,4-phenylene group having an ion exchange group.
[0046] Building block A 1 The repeat number (x) of the structure in [ ] in formula (a1) in the above formula is preferably 2 to 8, and more preferably 3 to 5, from the viewpoints of obtaining better proton conductivity and excellent hot water resistance.
[0047] Building block A1 From the viewpoint of obtaining better proton conductivity, it is preferable that the polyimide compound contains at least one structure selected from the group consisting of a structure represented by the following formula (a1-1) (hereinafter referred to as "structure (a1-1)") and a structure represented by the following formula (a1-2) (hereinafter referred to as "structure (a1-2)").
[0048] [ka]
[0049] [ka]
[0050] In formula (a1-1) and formula (a1-2), IExG and * are the same as defined above. Multiple IExG may be the same or different. x in formula (a1-1) 1 represents an integer of 2 to 10, and x in formula (a1-2) 2 represents an integer of 2 to 5. 1 If contains both structure (a1-1) and structure (a1-2), then x 1 and 2x 2 The sum of is 2 to 10. x 1 is preferably 2 to 5, and more preferably 2 to 3. 2 is preferably 2 to 3, and more preferably 2.
[0051] Building block A 1 may consist of only the structure (a1-1), or may contain the structure (a1-1) and a structure other than the structure (a1-1). In the latter case, the structure (a1-1) and the structure other than the structure (a1-1) are connected via a linking group (L 3 Similarly, the structural unit A may be linked by 1 may consist of only the structure (a1-2), or may contain the structure (a1-2) and a structure other than the structure (a1-2). In the latter case, the structure (a1-2) and the structure other than the structure (a1-2) are connected via a linking group (L 3 ) may be connected.
[0052] Building block A 1 Specific examples of the structural units include those represented by the following formulae (A1-1) to (A1-4).
[0053] [ka]
[0054] IExG and * in formulae (A1-1) to (A1-4), and L in formulae (A1-3) to (A1-4) 3 The multiple IExGs may be the same or different, and multiple L 3 may be the same or different from each other.
[0055] Structural unit A in polymer (P) 1 From the viewpoints of obtaining better proton conductivity and excellent chemical durability, the structural unit is preferably any one of the structural units represented by formulae (A1-1) to (A1-4), and more preferably a structural unit represented by formula (A1-2).
[0056] [Structural unit A 2 ] Building block A 2 is an arylene group (Ar) that does not have an ion exchange group and a linking group (L 4 ) and has a continuous structure.
[0057] The arylene group is a divalent aromatic hydrocarbon group, and has a structure in which two hydrogen atoms have been removed from an aromatic hydrocarbon. From the viewpoints of solubility in a solvent and film-forming properties, the number of aromatic rings in the arylene group is preferably 1 to 4, more preferably 1 to 2, and even more preferably 1. The arylene group may have a substituent other than an ion-exchange group, but preferably has no substituent.
[0058] Specific examples of the arylene group include a phenylene group, a naphthylene group, a fluorene group, an anthracylene group, a phenanthrylene group, a triphenylene group, a pyrenylene group, and a tetracenylene group.
[0059] Building block A 2 From the viewpoints of solubility in a solvent and film-forming properties, the structural unit A preferably contains, as an arylene group, at least one selected from the group consisting of a phenylene group, a naphthylene group, and a fluorene group, more preferably contains a phenylene group, and further preferably contains a 1,4-phenylene group. 2 It is more preferable that the majority of the arylene groups present in the structural unit A are those of the above-mentioned preferred embodiment. 2 It is particularly preferable that all of the arylene groups present in the copolymer are each independently a phenylene group, a naphthylene group or a fluorene group.
[0060] Building block A 2 From the viewpoints of excellent solubility in a solvent, excellent film-forming property, and excellent mechanical strength during film formation, 4 From the same viewpoint, the structural unit A preferably contains at least one group selected from the group consisting of -SO2-, -CO-, and a single bond, and more preferably contains -SO2- or -CO-. 2 There are multiple linking groups (L 4 It is more preferable that the majority of the structural units A 2 There are multiple linking groups (L 4 ) may all be of the preferred embodiments described above.
[0061] Building block A 2 The linking group (L 4 ) is preferably a single bond or -SO2- from the viewpoint of excellent chemical durability.
[0062] Building block A 2The repeat number (y) of the structure in [ ] in formula (a2) in the above formula is preferably 4 to 12, and more preferably 5 to 10, from the viewpoints of obtaining better proton conductivity and excellent hot water resistance.
[0063] Building block A 2 In order to achieve both better proton conductivity and hot water resistance, the repeat number (y) of the structure in [ ] in formula (a2) in this case is preferably a number (x+(2 to 7)) larger by 2 to 7 than the repeat number (x) of the structure in [ ] in formula (a1).
[0064] Building block A 2 From the viewpoints of excellent solubility in a solvent, excellent film-forming ability, and excellent mechanical strength during film formation, it is preferable for the compound to contain at least one structure selected from the group consisting of a structure represented by the following formula (a2-1) and a structure represented by the following formula (a2-2):
[0065] [ka]
[0066] [ka]
[0067] In the formula (a2-1) and the formula (a2-2), Ar and * have the same meaning as defined above. A plurality of Ar may be the same or different.
[0068] Building block A 2 A specific example of the structural unit is the structural unit represented by the following formula (A2).
[0069] [ka]
[0070] Ar and L in formula (A2) 4 and * are as defined above, Q represents a group having a structure represented by formula (a2-1) or formula (a2-2), y1 and y 2 Each independently represents an integer of 2 to 4. 1 and y 2 is preferably 2 to 3. A plurality of Ar may be the same or different, and a plurality of L 4 may be the same or different from each other.
[0071] [Linking group] The polymer (P) is made of the structural unit A from the viewpoint of obtaining superior proton conductivity and superior chemical durability. 1 and building block A 2 The linking group (L 1 Or L 2 ) preferably contains at least one group selected from the group consisting of a single bond, -SO2- and -S-, and more preferably contains -SO2-. From the same viewpoint, the structural units A present in multiple numbers in the polymer (P) 1 and building block A 2 The linking group (L 1 and L 2 It is more preferable that the majority of the structural units A) are those of the above-mentioned preferred embodiment, and 1 and building block A 2 The linking group (L 1 and L 2 It is particularly preferred that all of the above are of the preferred embodiments.
[0072] Structural unit A in polymer (P) 1 and building block A 2 The linking group (L 1 and L 2 ) are preferably each independently a single bond or -SO2- from the viewpoint of obtaining better proton conductivity and excellent chemical durability.
[0073] As described above, the polymer (P) is 1 and building block A 2 The linking group (L 1 and L 2 ) plus structural unit A 1 Medium and structural unit A2 There is also a linking group (L 3 and L 4 ), but from the viewpoint of obtaining superior proton conductivity and superior chemical durability, these linking groups (L 1 , L 2 , L 3 and L 4 ) are particularly preferably each independently a single bond or -SO2-.
[0074] The polymer (P) may be composed of a structure represented by formula (1) and a terminal structure bonded to the structure. The polymer (P) may be, for example, a compound represented by the following formulae (1-1) to (1-3).
[0075] [ka]
[0076] A in formulas (1-1) to (1-3) 1 , A 2 , L 1 , L 2 and n are as defined above. However, in formula (1-1) and formula (1-2), Z 2 L binds to 2 is a single bond. Z 1 and Z 2 are each independently a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkylborane group, or a boronic acid ester group. Examples of halogen atoms include a fluorine atom (F), a chlorine atom (Cl), a bromine atom (Br), and an iodine atom (I). Examples of alkylborane groups include a diethylborane group, a disiamylborane group, a dicyclohexylborane group, and a 9-borabicyclo[3.3.1]nonane group. Examples of boronic acid ester groups include a pinacol boronic acid ester group, a 1,3-propanediol boronic acid ester group, a biscyclohexyldiol boronic acid ester group, a neopentyl glycol boronic acid ester group, and a catechol boronic acid ester group.
[0077] The polymer (P) may contain a plurality of polymer units (hereinafter also referred to as "polymer units A") containing the structure represented by formula (1). For example, the polymer (P) may contain three or more polymer units A and a crosslinking group bonding to the three or more polymer units A. The polymer (P) having such a crosslinking group (hereinafter also referred to as "crosslinked polymer (P')") has excellent swelling resistance.
[0078] The polymer unit A can be, for example, a compound represented by any one of the above formulas (1-1) to (1-3) having a terminal group Z 1 and Z 2 Of the two terminal groups of the polymer unit A, the terminal group that bonds to the crosslinking group is A 1 A may be 2 The terminal group bonded to the crosslinking group may be L 2 (i.e., Z in formula (1-1) and formula (1-2) 2 L binds to 2 When the terminal group attached to the bridging group is A 2 The two end groups of the polymer unit A may be bonded to different crosslinking groups. Of the two end groups of the polymer unit A, the end group opposite to the end group bonded to the crosslinking group is considered to be the above-mentioned end group Z. 1 and Z 2 A plurality of polymer units A bonded to one crosslinking group may be the same or different.
[0079] The crosslinking group may be a group derived from a known crosslinking compound. From the viewpoint of chemical stability, the crosslinking group preferably has one or more aromatic rings. In this case, it is preferable that the polymer unit A is bonded to the aromatic ring of the crosslinking group. The polymer unit A may be bonded directly to the aromatic ring, or may be bonded to the aromatic ring via -O-, -S- or -SO2-. The number of aromatic rings in the crosslinking group is preferably 1 or 2.
[0080] The crosslinking group may be, for example, a group represented by the following formula (c):
[0081] [ka]
[0082] In formula (c), E represents a hydroxy group, a thiol group, a halogen atom, a boronic acid group, an alkylborane group, or a boronic acid ester group; 5 represents a single bond, -O-, -S-, -SO2- or -CO-; L 6 represents a single bond, -O-, -S- or -SO2-, * represents a bond bonded to the polymer unit A, p, q, r and s each represent an integer of 0 to 5, and z represents 0 or 1. However, p+q is 3 or more, p+r is 0 to 5, q+s is 0 to 5, and when z is 0, r and p are 0. When multiple E's are present, the multiple E's may be the same or different from each other. L 5 If there are multiple L 5 may be the same or different. 6 may be the same or different from each other.
[0083] The group represented by formula (c) may be, for example, a group represented by the following formulae (c1) to (c5). The symbols in formulae (c1) to (c5) have the same meanings as above. Some or all of E in the groups represented by formulae (c1) to (c5) may be replaced with a hydrogen atom.
[0084] [ka]
[0085] The number of crosslinking groups contained in the crosslinked polymer (P') may be one or more. The multiple crosslinking groups may be the same or different.
[0086] The crosslinked polymer (P') may contain a crosslinking group bonding to two polymer units A. Such a crosslinking group may have the same structure as the crosslinking group bonding to three or more polymer units A, except that the number of bonds bonding to the polymer unit A is different.
[0087] The proportion of the structure represented by formula (1) in the entire polymer (P) is preferably 80% by mass or more, from the viewpoint of obtaining better proton conductivity. From the same viewpoint, the proportion of the structure represented by formula (1) in the entire polymer (P) may be 85% by mass or more, or 90% by mass or more. The proportion of the structure represented by formula (1) in the entire polymer (P) may be less than 100% by mass. The proportion of the structure represented by formula (1) in the entire polymer (P) may be 80% by mass or more and less than 100% by mass, or 85% by mass or more and less than 100% by mass.
[0088] The polymer (P) may contain fluorine atoms, but the fluorine content in the polymer (P) is preferably 5 mass% or less, and it is preferable that the polymer (P) does not contain fluorine atoms (the fluorine content is below the detection limit).
[0089] The number average molecular weight of the polymer (P) may be 20,000 or more, 25,000 or more, or 30,000 or more from the viewpoints of superior proton conductivity and superior mechanical strength during film formation, and may be 300,000 or less, 200,000 or less, or 150,000 or less from the viewpoints of superior solubility in a solvent and film formability. From these viewpoints, the number average molecular weight of the polymer (P) may be 20,000 to 300,000, 25,000 to 200,000, or 30,000 to 150,000.
[0090] The weight average molecular weight of the polymer (P) may be 40,000 or more, 50,000 or more, or 60,000 or more from the viewpoints of superior proton conductivity and superior mechanical strength during film formation, and may be 500,000 or less, 300,000 or less, or 200,000 or less from the viewpoints of superior solubility in a solvent and superior film formability. From these viewpoints, the weight average molecular weight of the polymer (P) may be 40,000 to 500,000, 50,000 to 300,000, or 60,000 to 200,000.
[0091] The ratio of the weight average molecular weight to the number average molecular weight (polydispersity) of the polymer (P) may be 2.0 or more, 2.5 or more, or 2.8 or more. When the polydispersity of the polymer (P) is 2.5 or more, excellent swelling resistance tends to be obtained. From the viewpoint of solubility in a solvent, the polydispersity of the polymer (P) may be 20.0 or less, 15.0 or less, or 10.0 or less. The polydispersity of the polymer (P) may be 2.0 to 20.0, 2.5 to 20.0, 2.5 to 15.0, or 2.8 to 10.0.
[0092] The number average molecular weight and weight average molecular weight of the polymer (P) are values calculated as standard polyethylene glycol / oxide (PEG / PEO) as measured by gel permeation chromatography (GPC).
[0093] The polymer (P) can be obtained, for example, by reacting (polymerizing) a compound represented by the following formula (b1) (hereinafter also referred to as "compound (b1)") with a compound represented by the following formula (b2) (hereinafter also referred to as "compound (b2)"). That is, the polymer (P) can be a polymer of the compound (b1) and the compound (b2).
[0094] [ka]
[0095] In formula (b1), A 1 is as defined above, and X 1b and X 2b each independently represents a halogen atom. Examples of the halogen atom include a fluorine atom (F), a chlorine atom (Cl), a bromine atom (Br), and an iodine atom (I).
[0096] [ka]
[0097] In formula (b2), A 2 is as defined above, and Z 1b and Z2b each independently represents a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkylborane group, or a boronic acid ester group. Examples of the halogen atom, the alkylborane group, and the boronic acid ester group are the same as those described above. 1 and Z 2 These are the same as the examples of the halogen atom, alkylborane group and boronic acid ester group represented by the following formula:
[0098] In the above method, the structural unit A 1 and building block A 2 Therefore, according to the above method, the repeat number n in formula (1) can be easily increased to 10 or more.
[0099] According to the above method, L in formula (1) 1 and L 2 A polymer (P) is obtained in which Z is -O-, -S- or a single bond. 1b and Z 2b When at least one of the groups is a hydroxy group, L 1 and L 2 A polymer (P) is obtained in which at least one of Z is -O-. 1b and Z 2b When at least one of the groups is a thiol group, L 1 and L 2 A polymer (P) is obtained in which at least one of Z is -S-. 1b and Z 2b When at least one of the groups is a halogen atom, a boronic acid group, an alkylborane group, or a boronic acid ester group, L 1 and L 2 A polymer (P) is obtained in which at least one of the groups is a single bond.
[0100] The compound (b1) is X 1b and / or X 2b Similarly, as the compound (b2), Z 1b and / or Z 2bIt is possible to use multiple compounds with different
[0101] Compound (b1) and compound (b2) can be reacted (polymerized), for example, by an aromatic nucleophilic substitution reaction in a solvent in the presence of a base.
[0102] The solvent used in the reaction is preferably a good solvent for the compound (b1), the compound (b2), and the polymer (P), and capable of increasing the molecular weight of the polymer (P) during polymerization. For example, N-methyl-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethylsulfoxide, diphenylsulfone, sulfolane, 1,3-dimethyl-2-imidazolidinone, and tetramethylurea are preferably used. These solvents may be used alone or in a mixture of two or more kinds.
[0103] The base is used to improve the nucleophilicity of compound (b2). The base is not particularly limited as long as it can deprotonate compound (b2). For example, hydroxides and carbonates of alkali metals (lithium, sodium, potassium, rubidium, cesium), hydroxides and carbonates of alkaline earth metals (magnesium, calcium, strontium, barium), and organic bases such as amines can be used.
[0104] The reaction temperature may be in the range of 25° C. to 350° C. From the viewpoint of excellent reaction rate, the reaction temperature is preferably 60° C. or higher, and more preferably 100° C. or higher. From the viewpoint of suppressing decomposition of the polymer, the reaction temperature is preferably 300° C. or lower, and more preferably 250° C. or lower.
[0105] Compound (b1) and compound (b2) can also be reacted (polymerized) by, for example, a cross-coupling reaction in a solvent in the presence of a catalyst. Examples of solvents that can be used in the reaction are the same as the examples of solvents that can be used in the aromatic nucleophilic substitution reaction.
[0106] The catalyst is not particularly limited as long as it can promote the cross-coupling reaction, and a conventionally known catalyst can be used. For a coupling reaction between halogens, for example, a copper catalyst, a nickel catalyst, or a palladium catalyst can be used. For a coupling reaction between a halogen and a boronic acid group, an alkylborane group, or a boronic ester group, for example, a conventionally known catalyst (palladium catalyst, nickel catalyst, etc.) used in the Suzuki-Miyaura coupling reaction can be used.
[0107] Examples of copper catalysts include copper(I) 2-thiophenecarboxylate and copper(I) tetrakis(acetonitrile)hexafluorophosphate.
[0108] Examples of nickel catalysts include bis(1,5-cyclooctadiene)nickel(0), dibromobis(triphenylphosphine)nickel(II), and [1,1'-bis(diphenylphosphino)ferrocene]dichloronickel(II).
[0109] Examples of the palladium catalyst include tetrakis(triphenylphosphine)palladium(0), palladium(II) acetate, bis(triphenylphosphine)palladium(II) dichloride, and [1,1'-bis(diphenylphosphino)ferrocene]dichloropalladium(II).
[0110] The reaction temperature may be in the range of 0° C. to 350° C. From the viewpoint of excellent reaction rate, the reaction temperature is preferably 30° C. or higher, and more preferably 60° C. or higher. From the viewpoint of suppressing decomposition of the polymer, the reaction temperature is preferably 300° C. or lower, and more preferably 250° C. or lower.
[0111] In the aromatic nucleophilic substitution reaction and cross-coupling reaction, it is preferable to remove water from the reaction system in order to increase the molecular weight of the polymer (P). The dehydration method is not particularly limited, but for example, a method of azeotropic dehydration by making an azeotropic solvent coexist in the reaction system, a method of continuously removing water from the reaction system by heating above the boiling point of water, and a method of making a water absorbent such as a molecular sieve coexist can be used. The azeotropic solvent is not particularly limited as long as it can remove water, and examples thereof include benzene, toluene, cyclohexane, and xylene.
[0112] The aromatic nucleophilic substitution reaction and the cross-coupling reaction are preferably carried out under an inert atmosphere (for example, under a nitrogen atmosphere or an argon atmosphere). After the polymerization reaction is completed, the polymer is recovered from the reaction solution and purified to obtain the desired polymer. Examples of the method for recovering the polymer from the reaction solution include a method in which the reaction solution is added to a solvent in which the polymer has low solubility, and the polymer is precipitated as a solid and recovered, and a method in which the solvent is removed from the reaction solution by evaporation and the polymer is recovered as a solid. Examples of the method for purifying the polymer include a method of washing in a solvent in which the polymer has low solubility and in which by-produced inorganic salts and compounds derived from the remaining monomers have high solubility, and a washing method using a Soxhlet extractor. The method for recovering and purifying the polymer is not limited to these methods.
[0113] The polymer (P) can also be obtained by oxidizing a polymer having a structure represented by formula (1) (for example, a polymer of compound (b1) and compound (b2)). More specifically, the polymer (P) can be obtained by oxidizing a polymer having a structure represented by formula (1) in which L 1 , L 2 , L 3 Or L 4 The sulfide-containing polymer may be an oxide of a polymer containing -S- (sulfide group) as a substituent (hereinafter referred to as a "sulfide-containing polymer"). From the viewpoint of excellent chemical durability, the sulfide-containing polymer is a polymer having a structure represented by formula (1), 1 , L 2 , L 3 and L4 are each independently a single bond, -S- or -SO2-.
[0114] The method for oxidizing the sulfide-containing polymer is not particularly limited, and may be a known method for oxidizing a sulfide group (-S-) to obtain a sulfonyl group (-SO2-). Such a method may include, for example, a method of immersing the sulfide-containing polymer in a mixed solution containing acetic acid, sulfuric acid, and hydrogen peroxide. The concentration of acetic acid in the mixed solution may be, for example, 50 to 90 mass%. The concentration of sulfuric acid in the mixed solution may be, for example, 5 to 25 mass%. The concentration of hydrogen peroxide in the mixed solution may be, for example, 1 to 15 mass%. The immersion time may be, for example, 1 to 100 hours. In the above method, heating may be performed after immersion. The heating temperature may be, for example, 30 to 120°C, and the heating time may be, for example, 0.1 to 24 hours.
[0115] The polymer (P) obtained by the above method is a polymer having a structure represented by formula (1), L 1 , L 2 , L 3 Or L 4 The polymer contains -SO2- (sulfonyl group) as the substituent. The polymer may be one in which all of the sulfide groups in the sulfide-containing polymer are oxidized to sulfonyl groups (complete oxide), or one in which some of the sulfide groups in the sulfide-containing polymer are oxidized to sulfonyl groups (partial oxide). The degree of oxidation can be adjusted, for example, by the impregnation time, heating temperature, and heating time.
[0116] The polymer (P) can also be obtained by reacting (polymerizing) a polymer of compound (b1) and compound (b2) or an oxide thereof with a compound having three or more groups that react with the polymer or the oxide thereof to form a crosslink (hereinafter, also referred to as "crosslinkable compound (d)"). That is, the polymer (P) can be a reaction product of a polymer of compound (b1) and compound (b2) or an oxide thereof with the crosslinkable compound (d).
[0117] The above method can obtain a crosslinked product (for example, the above-mentioned crosslinked polymer (P')) having a polymer unit of a polymer of compound (b1) and compound (b2) or an oxide thereof. The above method can form a crosslinked structure while maintaining a precise sequence structure, and can achieve both excellent proton conductivity and excellent swelling resistance.
[0118] The crosslinkable compound (d) may be a known crosslinkable compound, for example, a low molecular weight compound having a molecular weight of not more than 1000. The group that reacts with the above-mentioned polymer or its oxide to form a crosslink is, for example, a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkylborane group, or a boronic acid ester group.
[0119] From the viewpoint of chemical stability, the crosslinkable compound (d) preferably has one or more aromatic rings. In this case, the group that reacts with the polymer or its oxide to form a crosslink is preferably directly bonded to the aromatic ring. The number of aromatic rings that the crosslinkable compound (d) has is preferably 1 or 2.
[0120] The crosslinkable compound (d) may be, for example, a compound represented by the following formula (d):
[0121] [ka]
[0122] In formula (d), E, L 5 and z are as defined above, and t and u each represent an integer of 0 to 5, provided that t+u is 3 or more, and when z is 0, t is 0. The multiple E's may be the same or different. Of the multiple E's, three or more E's are terminal groups (X 1b , X 2b , Z 1b or Z 2b ) to form crosslinks.
[0123] The polymer of the compound (b1) and the compound (b2) and the oxide thereof, and the crosslinkable compound (d) may each be used alone or in combination of two or more kinds.
[0124] The reaction of the polymer of compound (b1) and compound (b2) or the oxide thereof with the crosslinkable compound (d) can be carried out in the same manner as the reaction of compound (b1) with compound (b2).
[0125] <Electrolyte materials and electrolyte membranes> The electrolyte material of one embodiment is a material containing an electrolyte, and contains the above-mentioned polymer (P) as the electrolyte. The electrolyte membrane of one embodiment is a membrane containing an electrolyte, and contains the above-mentioned polymer (P) as the electrolyte. The electrolyte material is used to form the electrolyte membrane. That is, the electrolyte membrane may be made of the electrolyte material.
[0126] The electrolyte material and the electrolyte membrane have excellent proton conductivity because they contain the polymer (P).
[0127] The electrolyte material and the electrolyte membrane may also have a microphase-separated structure when immersed in water (wet state). Specifically, when the electrolyte membrane is immersed in water and subjected to small-angle X-ray scattering (SAXS) measurement, the peak interplanar spacing obtained may be 4.0 nm or more.
[0128] The electrolyte material and the electrolyte membrane may also have a microphase-separated structure in a vacuum-dried state (dry state). Specifically, when the electrolyte membrane is subjected to small-angle X-ray scattering (SAXS) measurement in a vacuum-dried state, the peak interplanar spacing obtained may be 2.5 nm or more.
[0129] The electrolyte material and the electrolyte membrane may consist of only the polymer (P), or may contain the polymer (P) and a component (additive, etc.) other than the polymer (P). That is, the electrolyte material may be a composition. The content of the polymer (P) in the electrolyte material and the electrolyte membrane may be 90 to 100 mass%, 94 to 100 mass%, or 97 to 100 mass%. The above content is based on the total solid content of the electrolyte material or the electrolyte membrane.
[0130] Components other than the polymer (P) that may be contained in the electrolyte material and the electrolyte membrane include water-retentive inorganic substances and radical scavengers, specifically, for example, water, silica, cerium oxide, and manganese oxide. These may be used alone or in combination.
[0131] The thickness of the electrolyte membrane is not particularly limited and can be changed depending on the size of the fuel cell, etc. From the viewpoint of increasing the mechanical strength of the membrane and reducing the membrane resistance, the thickness of the electrolyte membrane may be, for example, 1 to 200 μm, 1 to 100 μm, or 1 to 50 μm.
[0132] The method for producing the electrolyte membrane is not particularly limited, and the electrolyte membrane can be produced by a method known in the art for producing a membrane of an electrolyte polymer, such as a solution casting method, a dispersion casting method, a melt pressing method, or a melt extrusion method.
[0133] In the solution casting method, for example, a solution containing a polymer (P) is used as an electrolyte material, the solution is cast onto a substrate, the solvent is removed, and then the membrane is peeled off from the substrate to obtain an electrolyte membrane.
[0134] The solvent used in the solution casting method is not particularly limited as long as it can dissolve the polymer (P), and for example, N-methyl-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethylsulfoxide, diphenylsulfone, sulfolane, 1,3-dimethyl-2-imidazolidinone, and tetramethylurea can be used. These can be used alone or in combination.
[0135] In the dispersion casting method, for example, a dispersion containing a polymer (P) is used as an electrolyte material, and the dispersion is cast onto a substrate, the dispersion medium is removed, and then the membrane is peeled off from the substrate to obtain an electrolyte membrane.
[0136] The dispersion medium used in the dispersion casting method is not particularly limited as long as it is a dispersion medium capable of dispersing the polymer (P), and for example, water, ethers, alcohols, ketones, acetonitrile, nitromethane, toluene, xylene, chlorobenzene, and chloroform can be used. Examples of ethers include tetrahydrofuran and diethyl ether. Examples of alcohols include methanol, ethanol, 1-propanol, isopropyl alcohol, and 1-butanol. Examples of ketones include acetone and cyclohexanone. These may be used alone or in combination.
[0137] The electrolyte material and the electrolyte membrane are suitable for use in polymer electrolyte fuel cells and polymer electrolyte water electrolysis devices. The electrolyte material and the electrolyte membrane can also be used in redox flow batteries, electrochemical hydrogen pumps, chloralkali electrolysis devices, solid acid catalysts, membrane humidity control devices, gas separation membranes, and the like.
[0138] The electrolyte membrane can also be used by being attached to a microporous membrane, a nonwoven fabric, a mesh, etc. That is, another embodiment of the present disclosure is a laminate including an electrolyte membrane and another membrane (a microporous membrane, a nonwoven fabric, a mesh, etc.).
[0139] <Catalyst-coated electrolyte membrane> An electrolyte membrane with a catalyst layer in one embodiment includes the electrolyte membrane of the above embodiment and a catalyst layer disposed on one or both sides of the electrolyte membrane.
[0140] The catalyst layer is, for example, a layer composed of an anode catalyst or a cathode catalyst in a solid polymer fuel cell, a solid polymer water electrolysis device, etc. Hereinafter, a layer composed of an anode catalyst is referred to as an anode catalyst layer, and a layer composed of a cathode catalyst is referred to as a cathode catalyst layer.
[0141] The configuration of the catalyst layer is not particularly limited, and may be a conventionally known configuration as a catalyst layer (anode catalyst layer, cathode catalyst layer) of a polymer electrolyte fuel cell or a polymer electrolyte water electrolysis device. The catalyst layer may be formed of, for example, a conductive composition containing an anode catalyst or a cathode catalyst and a conductive material. The catalyst layer may contain an ionomer.
[0142] As the anode catalyst in a polymer electrolyte fuel cell, a metal catalyst capable of promoting the oxidation reaction of fuel such as hydrogen can be used, and as the anode catalyst in a polymer electrolyte water electrolysis device, a metal catalyst capable of promoting the oxygen generation reaction can be used, for example, platinum, gold, silver, palladium, iridium, rhodium, ruthenium, iron, cobalt, nickel, chromium, tungsten, manganese, vanadium, and alloys of two or more of these metals can be used. These metals may be used alone or in combination of two or more.
[0143] The cathode catalyst in the polymer electrolyte fuel cell may be a metal catalyst capable of promoting an oxygen reduction reaction, and the cathode catalyst in the polymer electrolyte water electrolysis device may be a metal catalyst capable of promoting a hydrogen generation reaction, such as platinum, gold, silver, palladium, iridium, rhodium, ruthenium, iron, cobalt, nickel, chromium, tungsten, manganese, and vanadium, or an alloy of two or more of these metals. These metals may be used alone or in combination.
[0144] Examples of the conductive material that can be used include carbon blacks such as furnace black, ketjen black, channel black, and acetylene black, activated carbon, and graphite. These may be used alone or in combination of two or more.
[0145] As the ionomer, a conventionally known material can be used, for example, an ionomer containing a perfluoro electrolyte can be used. Also, the above-mentioned polymer (P) can be used as the ionomer. As the ionomer, it is preferable to use a material with high oxygen permeability. There is no particular limit to the amount of ionomer added in the catalyst layer, but it is preferable to adjust the amount added within a range where oxygen diffusion is not easily inhibited.
[0146] The catalyst layer may further contain, as additives, a water repellent such as fluorinated carbon, and a binder such as a fluorine-containing resin or a hydrocarbon-based resin having a sulfone group.
[0147] A laminate having an anode catalyst layer and a cathode catalyst layer on both sides of an electrolyte membrane (e.g., a layer structure of "anode catalyst layer / electrolyte membrane / cathode catalyst layer") is also called a CCM (Catalyst Coated Membrane), and is suitably used in solid polymer electrolyte fuel cells and solid polymer electrolyte water electrolysis devices.
[0148] In the above embodiment, instead of the electrolyte membrane, a laminate including the other membranes (microporous membrane, nonwoven fabric, mesh, etc.) described above may be used.
[0149] <Membrane electrode assembly> A membrane electrode assembly of one embodiment includes the electrolyte membrane of the above embodiment and an electrode layer disposed on one or both sides of the electrolyte membrane.
[0150] The electrode layer includes, for example, the catalyst layer (anode catalyst layer or cathode catalyst layer) in the catalyst-layered electrolyte membrane of the above embodiment. Hereinafter, the electrode layer including the anode catalyst layer is referred to as the anode layer, and the electrode layer including the cathode catalyst layer is referred to as the cathode layer.
[0151] The configuration of the electrode layer is not particularly limited, and may be a conventionally known configuration as the electrode layer (anode layer, cathode layer) of a polymer electrolyte fuel cell or a polymer electrolyte water electrolysis device. The electrode layer may be composed of, for example, the above-mentioned catalyst layer (anode catalyst layer or cathode catalyst layer) and a gas diffusion substrate. When the catalyst layer itself has gas diffusion properties, the electrode layer may be composed of only the catalyst layer. For example, a porous membrane can be used as the gas diffusion substrate. As the gas diffusion substrate, a substrate having water repellency and electrical conductivity in addition to gas diffusion properties (for example, a carbon fiber substrate such as a carbon nonwoven fabric or carbon paper, or a titanium fiber sintered body) can also be used.
[0152] A laminate having an anode layer and a cathode layer as electrode layers on both sides of an electrolyte membrane (for example, a laminate having a layer structure of "gas diffusion substrate / anode catalyst layer / electrolyte membrane / cathode catalyst layer / gas diffusion substrate") is also called an MEA (Membrane Electrode Assembly), and is suitably used in solid polymer fuel cells and solid polymer water electrolysis devices.
[0153] In the above embodiment, instead of the electrolyte membrane, a laminate including the other membranes (microporous membrane, nonwoven fabric, mesh, etc.) described above may be used.
[0154] <Polymer electrolyte fuel cell> A polymer electrolyte fuel cell according to one embodiment includes the membrane electrode assembly according to the above embodiment.
[0155] The configuration of the polymer electrolyte fuel cell is not particularly limited, and may be a conventionally known configuration, except for using the membrane electrode assembly of the above embodiment. The polymer electrolyte fuel cell may, for example, include two or more membrane electrode assemblies. The two or more membrane electrode assemblies may be stacked (laminated) via a separator. As the separator, a conventionally known separator for polymer electrolyte fuel cells may be used.
[0156] <Solid polymer water electrolysis device> A solid polymer water electrolysis device of one embodiment includes the membrane electrode assembly of the above embodiment.
[0157] The configuration of the solid polymer water electrolysis device is not particularly limited, and may be a conventionally known configuration, except for the use of the membrane electrode assembly of the above embodiment. The solid polymer water electrolysis device may further include, for example, a power feeder on the outside of the membrane electrode assembly. Also, the solid polymer water electrolysis device may include two or more membrane electrode assemblies. EXAMPLES
[0158] The contents of the present disclosure will be described in more detail below using examples and comparative examples, but the present disclosure is not limited to the following examples.
[0159] <Synthesis Example 1> (Synthesis of hydrophilic monomer (M1)) A 10L flask equipped with a dropping funnel, a reflux condenser, and a mechanical stirrer was replaced with nitrogen, and 101g of 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl and 4L of dehydrated tetrahydrofuran were charged and stirring was started. The flask was cooled to -70°C in a methanol-dry ice bath, and 320mL of 2.6mol / L n-butyllithium-hexane solution was added dropwise. The flask was stirred for 1 hour while cooled in the bath. 40mL of sulfurous acid gas was introduced into the flask with nitrogen gas. The flask was stirred for 30 minutes while cooled in the bath. The bath was then removed and the internal temperature was raised to 0°C. The precipitated solid was filtered off by suction filtration and washed with 200mL of tetrahydrofuran. The collected solid was dissolved in 2L of pure water, 260mL of 35% hydrogen peroxide was added, and the mixture was stirred for 18 hours. The solid was removed by suction filtration, and 600g of sodium chloride was added to the collected filtrate. The precipitated white solid was collected by suction filtration and purified by recrystallization from water / isopropyl alcohol. The obtained solid was dried under reduced pressure to obtain a hydrophilic monomer represented by the following formula (M1). The yield was 65%.
[0160] [ka]
[0161] <Synthesis Example 2> (Synthesis of hydrophobic monomer (M2)) In a 200 mL flask equipped with a stirrer, a Dean-Stark tube, a reflux condenser, and a calcium chloride tube, 4.0 g of 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl, 14.8 g of [1,1'-biphenyl]-4,4'-diol, and 13.2 g of potassium carbonate were charged, and 50 mL of N,N-dimethylacetamide (DMAc) and 50 mL of toluene were added. The temperature was raised to 160 ° C in an oil bath while stirring, and heating and stirring were continued for 4 hours. Toluene was extracted from the Dean-Stark tube, and the temperature was raised to 180 ° C in an oil bath. After the temperature was raised, heating and stirring were continued for 8 hours. After the reaction solution was allowed to cool to room temperature, the reaction solution was poured into 200 mL of 10% hydrochloric acid, and the precipitated white solid was filtered off. The filtered solid was washed with 300 mL of ethanol and dried. The dried solid was purified by recrystallization from NMP / ethanol. The obtained solid was dried under reduced pressure to obtain a hydrophobic monomer (M2) represented by the following formula (M2) in a yield of 50%.
[0162] [ka]
[0163] <Synthesis Example 3> (Synthesis of hydrophobic monomer (M3)) A 500 mL flask equipped with a stirrer and a cooling tube was replaced with nitrogen. 41 g of 4,4'-thiobisbenzenethiol, 14 g of 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl, 80 mL of DMAc, and 4 g of potassium carbonate were added to the flask. The temperature was raised to 100°C in an oil bath while stirring, and heating and stirring were continued for 6 hours. After the reaction solution was allowed to cool, 100 mL of 1 M hydrochloric acid was added, and the precipitated solid was collected by suction filtration. The collected solid was dissolved in dichloromethane and purified by silica column chromatography using dichloromethane as a developing solvent. The fraction containing the target product was collected, and the solvent was removed by an evaporator. The obtained solid was purified by recrystallization from dichloromethane. The obtained solid was dried under reduced pressure to obtain a hydrophobic monomer (M3) represented by the following formula (M3). The yield was 40%.
[0164] [ka]
[0165] <Synthesis Example 4> (Synthesis of hydrophobic monomer (M4)) A 500 mL flask equipped with a stirrer and a condenser was purged with nitrogen. 20 g of anhydrous aluminum chloride, 10 g of isophthaloyl chloride, and 240 mL of 1,2-dichlorobenzene were added to the flask. 24 g of 3-bromo-1,1'-biphenyl was added dropwise while stirring the reaction solution. The reaction solution was heated to 40°C and continued to be heated and stirred for 3 hours. After the reaction solution was allowed to cool to room temperature, the reaction solution was added to 900 mL of ice-cooled 3% hydrochloric acid and continued to be stirred at room temperature for 18 hours. The precipitated white solid was collected by suction filtration and washed with ethanol. The obtained solid was dried under reduced pressure and used in the next reaction.
[0166] The obtained dry solid (0.80 g), 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenol (0.71 g), [1,1'-bis(diphenylphosphino)ferrocene]palladium(II) dichloride dichloromethane adduct (0.11 g), and sodium carbonate (0.57 g) were added to a 100 mL flask and substituted with nitrogen. Tetrahydrofuran (THF) (30 mL) was added, and the reaction solution was heated to 50°C while vigorously stirring. Heating and stirring were continued at 50°C for 22 hours. After the reaction solution was allowed to cool, chloroform (100 mL) and 5% hydrochloric acid (100 mL) were added, and the organic layer was collected. The solvent was removed using an evaporator, and ethyl acetate (20 mL) was added to suspend the mixture. The suspension was suction filtered, the filtrate was collected, and the solvent was removed using an evaporator to obtain an orange oily substance. The oily substance obtained was dissolved in ethyl acetate and purified by silica column chromatography using a mixed solvent of ethyl acetate / hexane = 1 / 1 (volume ratio) as the developing solvent. The fraction containing the target substance was collected, and the solvent was removed using an evaporator. The solid obtained was purified by recrystallization from hot toluene. The solid obtained was dried under reduced pressure to obtain a hydrophobic monomer (M4) represented by the following formula (M4). The yield was 60%.
[0167] [ka]
[0168] <Synthesis Example 5> (Synthesis of hydrophobic monomer (M5)) A hydrophobic monomer (M5) represented by the following formula (M5) was obtained in the same manner as in Synthesis Example 4, except that 0.96 g of 4'-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)biphenyl-4-ol was used instead of 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenol. The yield was 47%.
[0169] [ka]
[0170] <Synthesis Example 6> (Synthesis of hydrophobic monomer (M6)) A 500 mL flask equipped with a stirrer and a cooling tube was replaced with nitrogen. 9.5 g of 2,7-dibromo-9,9-diphenylfluorene, 12.1 g of 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenol, 19 g of potassium carbonate, 2.0 g of tetrakis(triphenylphosphine)palladium(0), and 250 mL of tetrahydrofuran were added to the flask. The reaction solution was heated to 90°C and stirred for 3 hours. After the reaction solution was cooled to room temperature, 200 mL of water and 500 mL of ethyl acetate were added and the organic layer was collected. The solvent was removed using an evaporator, and the resulting crude product was purified by silica column chromatography using a mixed solvent of ethyl acetate / hexane = 1 / 1 (volume ratio) as the developing solvent. The fraction containing the target product was collected, and the solvent was removed using an evaporator. The resulting solid was dried under reduced pressure to obtain a hydrophobic monomer (M6) represented by the following formula (M6). The yield was 53%.
[0171] [ka]
[0172] <Comparative Example 1> (Synthesis of polymer (P1)) In a 100mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 1.334g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 0.816g of disodium diphenylsulfone-4,4'-dichloro-3,3'-disulfonate, and 0.551g of potassium carbonate were added, and nitrogen substitution was performed. Then, 10mL of DMAc and 10mL of toluene were added. After heating to 160°C and reflux dehydration for 4 hours, the toluene was extracted from the Dean-Stark tube. The reaction solution was heated to 180°C and polymerization was performed for 21 hours. After cooling to room temperature, reprecipitation purification was performed from 300mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P1) having a structure represented by the following formula (P1). The yield was 90%. Note that n in formula (P1) was calculated from the number average molecular weight described below. The same applies to n in formulas (P2) to (P8) described later.
[0173] [ka] [In formula (P1), M represents Na, K or H, and n represents a positive number (about 31).]
[0174] (molecular weight measurement) The number average molecular weight (Mn) and weight average molecular weight (Mw) of the polymer (P1) were measured under the following conditions, and the polydispersity (Mw / Mn) was calculated. Mn was 39,000, Mw was 130,000, and Mw / Mn was 3.3.
[0175] [Measurement conditions] The number average molecular weight (Mn) and weight average molecular weight (Mw) were measured by GPC. The polymer (P1) was dissolved in an eluent (N,N-dimethylformamide solvent containing 10 mmol / L lithium bromide) at a concentration of 1 mg / mL to prepare a sample solution. The apparatus used was a Tosoh HLC-8320GPC. Two Tosoh TSKgel SuperAWM-H columns (inner diameter 6.0 mm, length 15 cm) were used. A differential refractometer detector was used. The flow rate was 0.6 mL / min and the temperature was 40°C. The number average molecular weight (Mn) and weight average molecular weight (Mw) were calculated in terms of standard polyethylene glycol / oxide (PEG / PEO). The polydispersity (Mw / Mn) was calculated by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn).
[0176] (Preparation of electrolyte membrane) The obtained polymer (P1) was dissolved in DMAc to obtain a solution containing 10% by mass of polymer (P1). The obtained solution was cast onto a glass substrate and dried at 60°C for 12 hours to obtain a membrane (thickness 24 μm). The membrane thickness was measured at 25 points on the surface using a PG-02 constant pressure thickness measuring device manufactured by TECLOCK CORPORATION, and the average value was used. The obtained membrane was immersed in 1 M hydrochloric acid for 24 hours to remove metal ions (Na + Or K + ) to proton (H + ), then it was immersed in pure water to thoroughly wash, and dried under reduced pressure to obtain a polymer electrolyte membrane of Comparative Example 1 (electrolyte membrane made of proton-substituted polymer (P1), membrane thickness 24 μm).
[0177] (evaluation) [Proton conductivity evaluation] The proton conductivity of the resulting polymer electrolyte membrane was measured by the following method. A Teflon (registered trademark) measuring cell (Scribner, BT-115) was used, and the prepared electrolyte membrane was placed in the cell in contact with four platinum wires. After holding at 70% relative humidity for 2 hours, the humidity was increased from 20% relative humidity, and DC resistance measurement was performed by the four-terminal method while maintaining the set humidity. The proton conductivity in the in-plane direction of the electrolyte membrane was calculated from the obtained resistance value, the thickness of the polymer electrolyte membrane, and the distance between the terminals. The proton conductivity of the polymer electrolyte membrane of this comparative example was 60 mS / cm (80°C, 100% relative humidity).
[0178] [Gas permeability test] The gas permeability of the resulting polymer electrolyte membrane was evaluated according to the gas permeability test method (JIS K 7126-2) using the constant pressure method. Specifically, first, the polymer electrolyte membrane was mounted in a state in which it was hermetically sealed between the two chambers of the permeation cell. Hydrogen, which is the measurement gas, was supplied to one side of the polymer electrolyte membrane, and Ar gas, which is the carrier gas, was supplied to the other side. The relative humidity was adjusted by the humidifier temperature of each supply gas and the cell temperature. The measurement gas that had permeated the polymer electrolyte membrane was supplied to a gas chromatograph together with the carrier gas, and the gas permeability was measured from the detection data and flow rate. The gas permeability (cm) was calculated from the obtained gas permeability and the thickness of the polymer electrolyte membrane. 3 mm / (cm 2 The hydrogen gas permeability of the polymer electrolyte membrane of this comparative example was calculated to be 0.71×10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C, relative humidity 60%).
[0179] [Small angle X-ray scattering (SAXS) measurement] Small angle X-ray scattering (SAXS) measurements of the polymer electrolyte membrane were carried out in a dry state (under vacuum) and in a wet state (immersed in water) according to the following conditions. Device name: Bruker Japan NanoSTAR Voltage / Current: 45kV / 120mA X-ray wavelength: Cu Kα ray Camera length: 104.3cm Exposure time: 60 minutes (dry state), 180 minutes (wet state)
[0180] For the obtained small-angle scattering profile, the peak top position q max Therefore, the interplanar spacing d(=2π / q max For the polymer electrolyte (P1), no small-angle scattering peak was observed in the dry state, but d = 4.0 nm in the wet state.
[0181] [Volume swelling ratio measurement] A 3 cm square membrane was punched out from the obtained polymer electrolyte membrane, and the punched membrane was immersed in 50 mL of pure water at 80°C for 1 hour. The dimensional change before and after immersion in pure water was measured to calculate the volume of the membrane. The volume swelling ratio was calculated by dividing the volume of the membrane after immersion in pure water by the volume of the membrane before immersion in pure water. The volume swelling ratio was 55%.
[0182] <Comparative Example 2> In Comparative Example 2, a commercially available Nafion was used as an evaluation sample. TM Using NR211 (film thickness 25 μm), various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) were performed in the same manner as in Comparative Example 1. The proton conductivity was 130 mS / cm (80° C., relative humidity 100%), and the hydrogen gas permeability was 1.03×10 -7 cm 3 mm / (cm 2 The surface tension was 1.0 s kPa (80°C, relative humidity 60%). The interplanar spacing d in the dry and wet states measured by SAXS was 3.3 nm and 5.3 nm, respectively. The volume swelling ratio was 61%. TM Using the volume swelling ratio of NR211 as a standard, an electrolyte membrane was evaluated to have excellent swelling resistance when its volume swelling ratio was 61% or less.
[0183] <Example 1> (Synthesis of polymer (P2)) In a 100mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.983g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 1.181g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 0.507g of potassium carbonate were added and nitrogen substitution was performed. Then, 10mL of dimethyl sulfoxide (DMSO) and 10mL of cyclohexane were added. After heating to 130°C and refluxing and dehydrating for 4 hours, the cyclohexane was extracted from the Dean-Stark tube. Polymerization was performed for 150 hours while heating at 130°C. After cooling the reaction solution to room temperature, reprecipitation purification was performed from 300mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P2) having a structure represented by the following formula (P2). The yield was 97%. The Mn of the polymer (P2) measured in the same manner as in Comparative Example 1 was 30,000, the Mw was 61,000, and the Mw / Mn was 2.0.
[0184] [ka] [In formula (P2), M represents Na, K or H, and n represents a positive number (about 20).]
[0185] (Preparation of electrolyte membrane) The obtained polymer (P2) was dissolved in DMSO to obtain a solution containing 10% by mass of polymer (P2). The obtained solution was cast onto a glass substrate and dried at 60° C. for 12 hours to obtain a membrane (thickness: 49 μm). The obtained membrane was immersed in 1 M hydrochloric acid for 24 hours to remove metal ions (Na + Or K + ) to proton (H + ), then it was immersed in pure water to thoroughly wash, and dried under reduced pressure to obtain the polymer electrolyte membrane of Example 1 (electrolyte membrane made of proton-substituted polymer (P2), membrane thickness 49 μm).
[0186] (evaluation) The polymer electrolyte membrane of this example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 231 mS / cm (80°C, relative humidity 100%), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen gas permeability was 0.15×10 -7 cm 3 mm / (cm 2 s kPa) (80°C, 60% relative humidity), and the polymer electrolyte membrane of this example is Nafion TM It was confirmed that the membrane had better gas barrier properties than NR211. In the SAXS measurement, as shown in FIG. 1, clear peaks were confirmed in both the dry and wet states. The interplanar spacing d in the dry and wet states by the SAXS measurement was 3.6 nm and 5.5 nm, respectively, and it was confirmed that the polymer electrolyte membrane of this example had a microphase separation structure in both the dry and wet states. The volume swelling ratio was 184%.
[0187] <Example 2> (Synthesis of polymer (P3)) In a 100mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 2.711g of the hydrophobic monomer (M3) obtained in Synthesis Example 3, 2.664g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 1.352g of potassium carbonate were added and nitrogen replacement was performed. Then, 25mL of DMSO and 25mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, cyclohexane was extracted from the Dean-Stark tube. The reaction solution was heated to 140°C and polymerization was performed for 260 hours. After cooling to room temperature, reprecipitation purification was performed from 500mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P3) having a structure represented by the following formula (P3). The yield was 88%. The Mn of the polymer (P3) measured in the same manner as in Comparative Example 1 was 33,000, the Mw was 75,000, and the Mw / Mn was 2.3.
[0188] [ka] [In formula (P3), M represents Na, K or H, and n represents a positive number (about 20).]
[0189] (Preparation of electrolyte membrane) Except for using the polymer (P3) instead of the polymer (P2), the polymer electrolyte membrane of Example 2 (electrolyte membrane made of proton-substituted polymer (P3)) was obtained in the same manner as in Example 1. The thickness of the polymer electrolyte membrane was 37 μm.
[0190] (evaluation) The polymer electrolyte membrane of this example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 185 mS / cm (80°C, relative humidity 100%), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen gas permeability was 0.14×10 -7 cm 3 mm / (cm 2 s kPa) (80°C, 60% relative humidity), and the polymer electrolyte membrane of this example is Nafion TM It was confirmed that the membrane had better gas barrier properties than NR211. The interplanar spacing d in the dry and wet states measured by SAXS was 3.9 nm and 5.4 nm, respectively, and it was confirmed that the polymer electrolyte membrane of this example had a microphase-separated structure in the dry and wet states. The volume swelling ratio was 94%.
[0191] <Example 3> (Synthesis of polymer (P4) and preparation of electrolyte membrane) The polymer (P3) obtained in Example 2 was dissolved in DMSO to obtain a solution containing 10% by mass of the polymer (P3). The obtained solution was cast onto a glass substrate and dried at 60° C. for 12 hours to obtain a film (thickness 37 μm). The obtained film was immersed in a mixed solution consisting of 80 mL of acetic acid, 8 mL of sulfuric acid, and 7 mL of hydrogen peroxide, and stirred at 30° C. for 48 hours. Thereafter, the mixture was heated and stirred at 105° C. for 10 minutes. The obtained film was immersed in pure water, thoroughly washed, and dried under reduced pressure to obtain a film (thickness 37 μm) made of the polymer (P4) having a structure represented by the following formula (P4). The Mn of the polymer (P4) measured in the same manner as above was 37000, the Mw was 84000, and the Mw / Mn was 2.3. When the infrared absorption spectrum of the polymer film before and after the oxidation reaction was measured, it was found to have a peak at 1570 cm -1 and 1470cm -1 The absorption peak at 1330 cm disappeared after oxidation. -1 The absorption peak intensity at 1570cm increased. -1 and 1470cm -1 The absorption peak at 1330 cm is due to the ring stretching vibration of the benzene ring with the -S- bond. -1 Since the absorption peak is due to the stretching vibration of the -SO2- bond, it was confirmed that the -S- bond was oxidized to a -SO2- bond by the oxidation reaction.
[0192] [ka] [In formula (P4), M represents Na, K or H, and n represents a positive number (about 20).]
[0193] The obtained membrane was immersed in 1M hydrochloric acid for 24 hours to remove metal ions (Na + Or K + ) to proton (H + ), then it was immersed in pure water to thoroughly wash, and dried under reduced pressure to obtain a polymer electrolyte membrane of Example 3 (electrolyte membrane made of proton-substituted polymer (P4), membrane thickness 37 μm).
[0194] (evaluation) The polymer electrolyte membrane of this example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 172 mS / cm (80°C, relative humidity 100%), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen gas permeability was 0.11×10 -7 cm 3 mm / (cm 2 s kPa) (80°C, 60% relative humidity), and the polymer electrolyte membrane of this example is Nafion TM It was confirmed that the membrane had better gas barrier properties than NR211. The interplanar spacing d in the dry and wet states measured by SAXS was 3.9 nm and 5.2 nm, respectively, and it was confirmed that the polymer electrolyte membrane of this example had a microphase-separated structure in the dry and wet states. The volume swelling ratio was 74%.
[0195] <Example 4> (Synthesis of polymer (P5)) In a 100mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.816g of the hydrophobic monomer (M4) obtained in Synthesis Example 4, 1.195g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 0.652g of potassium carbonate were added and nitrogen replacement was performed. Then, 10mL of DMSO and 10mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, cyclohexane was extracted from the Dean-Stark tube. The reaction solution was heated to 140°C and polymerization was performed for 100 hours. After cooling to room temperature, reprecipitation purification was performed from 300mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P5) having a structure represented by the following formula (P5). The yield was 85%. The Mn of the polymer (P5) measured in the same manner as in Comparative Example 1 was 28,000, the Mw was 66,000, and the Mw / Mn was 2.4.
[0196] [ka] [In formula (P5), M represents Na, K or H, and n represents a positive number (about 20).]
[0197] (Preparation of electrolyte membrane) Except for using the polymer (P5) instead of the polymer (P2), the polymer electrolyte membrane of Example 4 (electrolyte membrane made of proton-substituted polymer (P5)) was obtained in the same manner as in Example 1. The thickness of the polymer electrolyte membrane was 31 μm.
[0198] (evaluation) The polymer electrolyte membrane of this example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 232 mS / cm (80°C, relative humidity 100%), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen gas permeability was 0.13×10 -7 cm 3 mm / (cm 2 s kPa) (80°C, 60% relative humidity), and the polymer electrolyte membrane of this example is Nafion TM It was confirmed that the membrane had better gas barrier properties than NR211. The interplanar spacing d in the dry and wet states measured by SAXS was 3.4 nm and 5.2 nm, respectively, and it was confirmed that the polymer electrolyte membrane of this example had a microphase-separated structure in the dry and wet states. The volume swelling ratio was 506%.
[0199] <Example 5> (Synthesis of polymer (P6)) In a 100mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.924g of the hydrophobic monomer (M5) obtained in Synthesis Example 5, 1.087g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 0.593g of potassium carbonate were added and nitrogen replacement was performed. Then, 10mL of DMSO and 10mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, cyclohexane was extracted from the Dean-Stark tube. The reaction solution was heated to 150°C and polymerization was performed for 120 hours. After cooling to room temperature, reprecipitation purification was performed from 300mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P6) having a structure represented by the following formula (P6). The yield was 94%. The Mn of the polymer (P6) measured in the same manner as in Comparative Example 1 was 29,000, the Mw was 59,000, and the Mw / Mn was 2.0.
[0200] [ka] [In formula (P6), M represents Na, K or H, and n represents a positive number (about 20).]
[0201] (Preparation of electrolyte membrane) Except for using the polymer (P6) instead of the polymer (P2), the polymer electrolyte membrane of Example 5 (electrolyte membrane made of proton-substituted polymer (P6)) was obtained in the same manner as in Example 1. The thickness of the electrolyte membrane was 52 μm.
[0202] (evaluation) The polymer electrolyte membrane of this example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 188 mS / cm (80°C, relative humidity 100%), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen gas permeability was 0.11×10 -7 cm 3 mm / (cm 2s kPa) (80°C, 60% relative humidity), and the polymer electrolyte membrane of this example is Nafion TM It was confirmed that the membrane had better gas barrier properties than NR211. The interplanar spacing d in the dry and wet states measured by SAXS was 3.8 nm and 5.6 nm, respectively, and it was confirmed that the polymer electrolyte membrane of this example had a microphase-separated structure in the dry and wet states. The volume swelling ratio was 114%.
[0203] <Example 6> (Synthesis of polymer (P7)) In a 100mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.932g of the hydrophobic monomer (M6) obtained in Synthesis Example 6, 1.297g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 0.593g of potassium carbonate were added and nitrogen replacement was performed. Then, 10mL of DMSO and 10mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, cyclohexane was extracted from the Dean-Stark tube. The reaction solution was heated to 150°C and polymerization was performed for 105 hours. After cooling to room temperature, reprecipitation purification was performed from 300mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P7) having a structure represented by the following formula (P7). The yield was 90%. The Mn of the polymer (P7) measured in the same manner as in Comparative Example 1 was 51,000, the Mw was 110,000, and the Mw / Mn was 2.2.
[0204] [ka] [In formula (P7), M represents Na, K or H, and n represents a positive number (about 30).]
[0205] (Preparation of electrolyte membrane) Except for using the polymer (P7) instead of the polymer (P2), the polymer electrolyte membrane of Example 6 (electrolyte membrane made of proton-substituted polymer (P7)) was obtained in the same manner as in Example 1. The thickness of the electrolyte membrane was 27 μm.
[0206] (evaluation) The polymer electrolyte membrane of this example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 199 mS / cm (80°C, relative humidity 100%), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen gas permeability was 0.12×10 -7 cm 3 mm / (cm 2 s kPa) (80°C, 60% relative humidity), and the polymer electrolyte membrane of this example is Nafion TM It was confirmed that the polymer electrolyte membrane of this example has better gas barrier properties than NR211. The interplanar spacing d in the dry and wet states measured by SAXS was 3.7 nm and 5.5 nm, respectively, and it was confirmed that the polymer electrolyte membrane of this example has a microphase-separated structure in the dry and wet states. The volume swelling ratio was 47%, and it was confirmed that the polymer electrolyte membrane of this example has excellent swelling resistance.
[0207] <Comparative Example 3> (Synthesis of polymer (P8)) In a 100 mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.498 g of 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl, 0.532 g of [1,1'-biphenyl]-4,4'-diol, 1.026 g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 1.185 g of potassium carbonate were added, and nitrogen replacement was performed. Then, 10 mL of DMSO and 10 mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, cyclohexane was extracted from the Dean-Stark tube. Polymerization was performed for 72 hours while heating at 130°C. After cooling the reaction solution to room temperature, reprecipitation purification was performed from 300 mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P8) having a structure represented by the following formula (P8). The yield was 94%. The Mn of the polymer (P8) measured in the same manner as in Comparative Example 1 was 26,000, the Mw was 69,000, and the Mw / Mn was 2.7.
[0208] [ka] [In formula (P8), M represents Na, K, or H, l is about 0.39 (0.35 or more and 0.43 or less), m is about 0.61 (0.57 or more and 0.65 or less), and n is about 40 (15 or more and 100 or less).]
[0209] (Preparation of electrolyte membrane) Except for using the polymer (P8) instead of the polymer (P2), a polymer electrolyte membrane of Comparative Example 3 (an electrolyte membrane made of a proton-substituted polymer (P8)) was obtained in the same manner as in Example 1. The thickness of the polymer electrolyte membrane was 48 μm.
[0210] (evaluation) The polymer electrolyte membrane of this comparative example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 113 mS / cm (80°C, relative humidity 100%), and the hydrogen gas permeability was 0.18×10-7 cm 3 mm / (cm 2 The temperature was 80°C and the relative humidity was 60%. In the SAXS measurement, no clear scattering peaks were observed in either the dry or wet state. The volume swelling ratio was 167%.
[0211] <Example 7> (Synthesis of polymer (P9)) In a 100mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.985g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 1.157g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 0.668g of potassium carbonate were added and nitrogen substitution was performed. Then, 10mL of dimethyl sulfoxide (DMSO) and 10mL of cyclohexane were added. After heating to 130°C and refluxing and dehydrating for 4 hours, the cyclohexane was extracted from the Dean-Stark tube. Polymerization was performed for 72 hours while heating at 130°C. Then, 0.004g of decafluorobiphenyl was added, and polymerization was performed for 3.5 hours while heating at 130°C. After cooling the reaction solution to room temperature, reprecipitation purification was performed from 300mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P9) containing a plurality of polymer units containing a structure represented by formula (P2) and having a crosslinking group derived from decafluorobiphenyl bonded to three or more of the polymer units. The yield was 81.9%. The Mn of the polymer (P9) measured in the same manner as in Comparative Example 1 was 54,000, the Mw was 150,000, and the Mw / Mn was 2.8.
[0212] (Fluorine content measurement) The fluorine content of the polymer (P9) was measured by the following method. First, the combustion gas generated by burning the sample (polymer (P9)) was blown into an aqueous hydrogen peroxide solution, and the fluorine content was absorbed into the aqueous solution to obtain an absorbing solution. Next, the same operation was performed without adding the sample to obtain a blank absorbing solution. The fluorine content was quantified by ion chromatography (IC) measurement using the obtained absorbing solution, the blank absorbing solution, and the original solution of the absorbing solution. The fluorine content of the polymer (P9) was 0.1 mass% or less.
[0213] (Preparation of electrolyte membrane) Except for using the polymer (P9) instead of the polymer (P2), the polymer electrolyte membrane of Example 7 (electrolyte membrane made of proton-substituted polymer (P9)) was obtained in the same manner as in Example 1. The thickness of the electrolyte membrane was 62 μm.
[0214] (evaluation) The polymer electrolyte membrane of this example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 200 mS / cm (80°C, relative humidity 100%), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen gas permeability was 0.13×10 -7 cm 3 mm / (cm 2 s kPa) (80°C, 60% relative humidity), and the polymer electrolyte membrane of this example is Nafion TM It was confirmed that the polymer electrolyte membrane of this example has better gas barrier properties than NR211. The interplanar spacing d in the dry and wet states by SAXS measurement was 4.0 nm and 5.0 nm, respectively, and it was confirmed that the polymer electrolyte membrane of this example has a microphase-separated structure in the dry and wet states. The volume swelling ratio was 60%, and it was confirmed that the polymer electrolyte membrane of this example has excellent swelling resistance.
[0215] <Example 8> (Synthesis of polymer (P10)) In a 100mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 2.955g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 3.526g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 2.051g of potassium carbonate were added and nitrogen substitution was performed. Then, 30mL of dimethyl sulfoxide (DMSO) and 30mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, cyclohexane was extracted from the Dean-Stark tube. Polymerization was performed for 72 hours while heating at 130°C. After that, the temperature was lowered to room temperature, 0.014g of decafluorobiphenyl was added, and polymerization was performed for 3.5 hours by heating to 130°C. After cooling the reaction solution to room temperature, reprecipitation purification was performed from 1000mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P10) containing a plurality of polymer units containing a structure represented by formula (P2) and having a crosslinking group derived from decafluorobiphenyl bonded to three or more of the polymer units. The yield was 79.3%. The Mn of the polymer (P10) measured in the same manner as in Comparative Example 1 was 71000, the Mw was 200000, and the Mw / Mn was 2.8. The fluorine content of the polymer P(10) measured in the same manner as in Example 7 was 0.1% by mass or less.
[0216] (Preparation of electrolyte membrane) Except for using the polymer (P10) instead of the polymer (P2), the polymer electrolyte membrane of Example 8 (electrolyte membrane made of proton-substituted polymer (P10)) was obtained in the same manner as in Example 1. The thickness of the electrolyte membrane was 56 μm.
[0217] (evaluation) The polymer electrolyte membrane of this example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 221 mS / cm (80°C, relative humidity 100%), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen gas permeability was 0.12×10 -7 cm 3 mm / (cm 2s kPa) (80°C, 60% relative humidity), and the polymer electrolyte membrane of this example is Nafion TM It was confirmed that the polymer electrolyte membrane of this example has better gas barrier properties than NR211. The interplanar spacing d in the dry and wet states by SAXS measurement was 4.0 nm and 4.9 nm, respectively, and it was confirmed that the polymer electrolyte membrane of this example has a microphase-separated structure in the dry and wet states. The volume swelling ratio was 58%, and it was confirmed that the polymer electrolyte membrane of this example has excellent swelling resistance.
[0218] <Example 9> (Synthesis of polymer (P11)) In a 100mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.982g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 1.139g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 1.442g of potassium carbonate were added and nitrogen substitution was performed. Then, 10mL of dimethyl sulfoxide (DMSO) and 10mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, cyclohexane was extracted from the Dean-Stark tube. Polymerization was performed for 72 hours while heating at 130°C. After that, the temperature was lowered to room temperature, 0.004g of decafluorobiphenyl was added, and the mixture was heated to 130°C and polymerized for 3.5 hours. After cooling the reaction solution to room temperature, reprecipitation purification was performed from 300mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P11) containing a plurality of polymer units containing a structure represented by formula (P2) and having a crosslinking group derived from decafluorobiphenyl bonded to three or more of the polymer units. The yield was 78.3%. The Mn of the polymer (P11) measured in the same manner as in Comparative Example 1 was 48,000, the Mw was 230,000, and the Mw / Mn was 4.8. The fluorine content of the polymer P(11) measured in the same manner as in Example 7 was 0.1% by mass or less.
[0219] (Preparation of electrolyte membrane) Except for using the polymer (P11) instead of the polymer (P2), the polymer electrolyte membrane of Example 9 (electrolyte membrane made of proton-substituted polymer (P11)) was obtained in the same manner as in Example 1. The thickness of the electrolyte membrane was 25 μm.
[0220] (evaluation) The polymer electrolyte membrane of this example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 203 mS / cm (80°C, relative humidity 100%), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen gas permeability was 0.16×10 -7 cm 3 mm / (cm 2 s kPa) (80°C, 60% relative humidity), and the polymer electrolyte membrane of this example is Nafion TM It was confirmed that the polymer electrolyte membrane of this example has better gas barrier properties than NR211. The interplanar spacing d in the dry and wet states measured by SAXS was 4.0 nm and 4.9 nm, respectively, and it was confirmed that the polymer electrolyte membrane of this example has a microphase-separated structure in the dry and wet states. The volume swelling ratio was 55%, and it was confirmed that the polymer electrolyte membrane of this example has excellent swelling resistance.
[0221] <Comparative Example 4> (Synthesis of polymer (P12)) In a 100mL three-neck flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 1.004g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 1.182g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, 0.004g of decafluorobiphenyl, and 0.673g of potassium carbonate were added and nitrogen substitution was performed. Then, 10mL of dimethyl sulfoxide (DMSO) and 10mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, cyclohexane was extracted from the Dean-Stark tube. Polymerization was performed for 72 hours while heating at 130°C. After cooling the reaction solution to room temperature, reprecipitation purification was performed from 300mL of isopropyl alcohol (IPA), and the solid was collected by suction filtration. The collected solid was washed with water and dried under reduced pressure to obtain a polymer (P12) having a crosslinked structure. The yield was 59.2%. The Mn, Mw and Mw / Mn of the polymer (P12) measured in the same manner as in Comparative Example 1 were 47000, 200000 and 4.3, respectively. In this synthesis example, the crosslinking agent decafluorobiphenyl was reacted with the hydrophilic monomer (M1) and the hydrophobic monomer (M2) simultaneously, so that the polymer (P12) has a structure in which the constitutional units derived from the hydrophilic monomer (M1), the constitutional units derived from the hydrophobic monomer (M2) and the crosslinkable groups derived from the decafluorobiphenyl are randomly arranged.
[0222] (Preparation of electrolyte membrane) Except for using the polymer (P12) instead of the polymer (P2), a polymer electrolyte membrane of Comparative Example 4 (an electrolyte membrane made of a proton-substituted polymer (P12)) was obtained in the same manner as in Example 1. The thickness of the polymer electrolyte membrane was 63 μm.
[0223] (evaluation) The polymer electrolyte membrane of this comparative example was subjected to various evaluations (proton conductivity evaluation, hydrogen gas permeability test, SAXS measurement, and volume swelling ratio measurement) in the same manner as in Comparative Example 1. The proton conductivity was 179 mS / cm (80°C, relative humidity 100%), and the hydrogen gas permeability was 0.11×10 -7 cm 3 mm / (cm 2The temperature was 80°C and the relative humidity was 60%. In the SAXS measurement, no clear scattering peaks were observed in either the dry or wet state. The volume swelling ratio was 81%. By comparing Example 7 with Comparative Example 4, it was confirmed that crosslinking at the polymer terminals improves the swelling suppression effect and proton conductivity due to crosslinking compared to polymers in which the crosslinks are spaced randomly.
[0224] [Table 1]
[0225] This application is based on a Japanese patent application (Patent Application No. 2023-55171) filed on March 30, 2023, and a Japanese patent application (Patent Application No. 2024-11288) filed on January 29, 2024, the entire contents of which are incorporated by reference. In addition, all references cited herein are incorporated in their entirety.
Claims
1. It has a structure represented by the following formula (1): 【Chemistry 1】 [In formula (1), A 1 represents a structural unit represented by the following formula (a1): A 2 represents a structural unit represented by the following formula (a2): L 1 and L 2 each independently represents a single bond, —O—, —S—, or —SO 2 - indicates n represents an integer from 10 to 100; * indicates a bond. Multiple A's 1 are identical to each other, Multiple A's 2 are identical to each other, Multiple L 1 may be the same or different, Multiple L 2 may be the same or different. 【Chemistry 2】 [In formula (a1), IExG represents an ion exchange group; L 3 represents a single bond, -O-, -S-, or -SO 2 - or -CO-, x represents an integer from 2 to 10; * indicates a bond. The multiple IExGs may be the same or different from each other, Multiple L 3 may be the same or different. 【Chemistry 3】 [In formula (a2), Ar represents an arylene group having no ion exchange group; L 4 represents a single bond, -O-, -S-, or -SO 2 - or -CO-, y represents an integer from 3 to 20; * indicates a bond. A plurality of Ar may be the same or different, Multiple L 4 may be the same or different. A polymer which is a reaction product of a polymer of a compound represented by the following formula (b1) and a compound represented by the following formula (b2) or an oxide thereof, and a compound having three or more groups which react with the polymer or the oxide thereof to form a crosslink: 【Chemistry 4】 [In formula (b1), A 1 is as defined above, and X 1b and X 2b each independently represents a halogen atom. 【Chemistry 5】 [In formula (b2), A 2 is as defined above, and Z 1b and Z 2b each independently represents a hydroxy group, a thiol group, a halogen atom, a boronic acid group, an alkylborane group, or a boronic acid ester group.
2. Said L 1 , said L 2 , said L 3 and the L 4 each independently represents a single bond or -SO 2 The polymer of claim 1, wherein
3. 3. The polymer according to claim 1, wherein the constitutional unit represented by formula (a1) contains, as the ion exchange group, at least one selected from the group consisting of a sulfone group, an alkylsulfone group, and a sulfonimide group.
4. 3. The polymer according to claim 1, wherein the constitutional unit represented by formula (a2) contains, as the arylene group, at least one selected from the group consisting of a phenylene group, a naphthylene group, and a fluorene group.
5. 3. The polymer according to claim 1, having a number average molecular weight of from 20,000 to 300,000.
6. 3. The polymer of claim 1, wherein the ratio of weight average molecular weight to number average molecular weight is from 2.0 to 20.
0.
7. An electrolyte material comprising the polymer according to claim 1 or 2.
8. An electrolyte membrane comprising the polymer according to claim 1 or 2.
9. A catalyst layer-coated electrolyte membrane comprising the electrolyte membrane according to claim 8 and a catalyst layer disposed on one or both sides of the electrolyte membrane.
10. A membrane electrode assembly comprising the electrolyte membrane according to claim 8 and an electrode layer disposed on one or both sides of the electrolyte membrane.
11. A polymer electrolyte fuel cell comprising the membrane electrode assembly according to claim 10.
12. A solid polymer water electrolysis device comprising the membrane electrode assembly according to claim 10.
Citation Information
Patent Citations
Polysulfone and biphenyl type sulfonated polyether sulfone as well as preparation method and application thereof
CN107602860A
Block copolymer, electrolyte membrane for fuel cell, membrane-electrode assembly, and solid polymer type fuel cell
JP2009191123A
Solid polymer electrolyte for fuel cell
JP2009252471A
Polymer electrolyte and method for producing the same
JP2013203919A
Polymer electrolyte and usage of the same
JP2015214617A
Cited By
JPWO2024204267A1